2021
DOI: 10.3390/cancers13164121
|View full text |Cite
|
Sign up to set email alerts
|

Can the New and Old Drugs Exert an Immunomodulatory Effect in Acute Myeloid Leukemia?

Abstract: Acute myeloid leukemia (AML) is considered an immune-suppressive neoplasm capable of evading immune surveillance through cellular and environmental players. Increasing knowledge of the immune system (IS) status at diagnosis seems to suggest ever more attention of the crosstalk between the leukemic clone and its immunologic counterpart. During the last years, the advent of novel immunotherapeutic strategies has revealed the importance of immune dysregulation and suppression for leukemia fitness. Considering all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 143 publications
(183 reference statements)
0
2
1
Order By: Relevance
“…Otherwise, it can be explained that the higher dose of ATG used in HID transplantation, compared with MSD or UD transplantation, in our study could be a cause of the more frequent CMV infections, which is supported by recent data showing a similar frequency of CMV infections in MUD and HID when using the same RIC regimen and ATG dose [ 36 ]. Nevertheless, despite concerns about the immunosuppressive effects of venetoclax [ 37 , 38 ], the incidence of CMV infection observed in this study was not higher than that with post-IC transplantation reported in other studies [ 20 , 28 , 35 ]. As suggested with GVHD complications, traditional risk factors, such as donor type and ATG dosage, are likely to play a greater role in the occurrence of post-transplant infectious complications than the regimens used prior to allo-HCT.…”
Section: Discussioncontrasting
confidence: 74%
“…Otherwise, it can be explained that the higher dose of ATG used in HID transplantation, compared with MSD or UD transplantation, in our study could be a cause of the more frequent CMV infections, which is supported by recent data showing a similar frequency of CMV infections in MUD and HID when using the same RIC regimen and ATG dose [ 36 ]. Nevertheless, despite concerns about the immunosuppressive effects of venetoclax [ 37 , 38 ], the incidence of CMV infection observed in this study was not higher than that with post-IC transplantation reported in other studies [ 20 , 28 , 35 ]. As suggested with GVHD complications, traditional risk factors, such as donor type and ATG dosage, are likely to play a greater role in the occurrence of post-transplant infectious complications than the regimens used prior to allo-HCT.…”
Section: Discussioncontrasting
confidence: 74%
“…Traditionally, new drugs have been tested in newly diagnosed cases of acute myeloid leukemia with relapse or at risk of disadvantage [ 12 , 49 51 ]. One possibility is on the MRD setting.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments for AL are focused on the direct elimination of tumor cells and, more recently, on the activating of the antitumor immune response [ 22 , 23 ]. However, other therapies, such as phytomedicines, can have a simultaneous effect on leukemic and microenvironment cells due to their multimolecular nature [ 24 , 25 , 26 ]; furthermore, in synergy with conventional therapy, they can improve the therapeutic response by reducing its toxicity and limiting the secondary effects of chemotherapy [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%